O desenho linguagem nas atividades da rotina escolar de criança com TEA em três escolas municipais feirense: 2020 e 2021 - Souza, Karla de Jesus (2023)
This work aimed to identify and analyze how drawing and drawing were part of the school life of students with Autistic Spectrum Disorder (ASD) during face-to-face and non-face-to-face teaching in municipal schools in Feira de Santana-BA, in the period of 2020 to 2021, amid the covid-19 pandemic. For this, the drawings in the activities proposed in three municipal schools feirense that work with the school inclusion of children with ASD were analyzed. Methodologically, a qualitative approach was chosen, developing in the form of non-participatory research, due to the impossibility of going to the field in person due to the pandemic. The research participants were two teachers and a psycho pedagogue from three public schools in Feira de Santana, which had autistic children enrolled in the segment of Early Childhood Education and Elementary School early years in their classrooms. Online questionnaire prepared from Google Forms and the collection of activities planned by the teachers for children with ASD that involved drawing as a means of obtaining answers. The results showed that drawing was present in the school routine, and that the activities carried out were the same for all students. However, some needed adaptations to be more inclusive and focused on the reality of each child, being elaborated in different supports. The study showed that drawing activities as a language allow the children to express themselves freely, and drawing creates conditions that awaken cognitive, social and motor skills, especially for children with ASD, sharpening the imagination, enabling communication and interaction, elements essential to life in society.